Jigsaw, Think-Pair-Share and Coop-Coop Cooperative Instructional Strategies and Retention of Students’ Knowledge in Carbohydrate - Comfort Daiko; Emmanuel E. Achor; Gladys U. Jack (EDUPEDIA PUBLISHER, 2023)
Purpose: This paper aims to compare the effects of Jigsaw, Think-pair-share, and Coop-Coop Cooperative Instructional Strategies on the retention of students' knowledge in Carbohydrate in Jalingo metropolis, Taraba State, Nigeria. Methodology: The study employed a quasi-experimental non-randomized pre-test, post-test design. The study population comprised 1936 students in all 41 public secondary schools in Jalingo metropolis, Taraba State, Nigeria. The sample consisted of 322 students (males = 184, females = 138) drawn from the population. An Achievement Test in Carbohydrate (ATC), consisting of 50 multiple-choice questions, was used to collect data for the study. The reliability index of the ATC was estimated using Kuder-Richardson (K-20) and yielded a value of .86. Both descriptive statistics, including Mean and standard deviation, and inferential statistics, such as Analysis of Covariance, were adopted for the analysis. Findings: Findings revealed that students taught carbohydrates using Jigsaw retained knowledge more than their counterparts taught using think-pair-share and coop-coop cooperative instructional strategies. Significance: There was no significant difference between the mean retention scores of male and female students taught carbohydrates using Jigsaw, Think-pair-share, and Coop–Coop Cooperative Instructional Strategies. The interaction effects between instructional strategies and gender on retention were not statistically significant. Among other recommendations, it was suggested that there is a need for an urgent workshop to address the use of Jigsaw to teach organic concepts and operations to enable chemistry teachers to deploy it appropriately.